Phytochemical Extracts of Dittrichia viscosa (L.) Greuter from Agroecological Systems: Seed Antigerminative Properties and Effectiveness in Counteracting Alternaria Leaf Spot Disease on Baby-Leaf Spinach - Catello Pane; Gelsomina Manganiello; Antonella Vitti; Rita Celano; Anna Lisa Piccinelli; Enrica De Falco (Biology, 2023)
Dittrichia viscosa (L.) Greuter subsp. viscosa (Asteraceae) is a perennial species naturally distributed in arid and marginal areas whose agroecological cultivation could be a useful innovation to produce quality biomass to extract phenolic-rich phytochemical blends. Here, biomass-yield trends were profiled at different growth stages under direct cropping, and inflorescences, leaves, and stems were submitted to water extraction and hydrodistillation. Then, four extracts were investigated for their biological activities in invitro and in planta assays. Extracts inhibited cress (Lepidium sativum)- and radish (Raphanus sativus)-seed germination and root elongation. All samples showed dose-dependent antifungal activity in the plate experiments, inhibiting up to 65% of the growth of the fungal pathogen Alternaria alternata, a leaf-spot disease agent of baby spinach (Spinacea oleracea). However, only the extracts from dried green parts and fresh inflorescences at the highest concentration significantly reduced (54%) the extent of Alternaria necrosis on baby spinach. UHPLC-HRMS/MS analysis revealed that the main specialized metabolites of the extracts are caffeoyl quinic acids, methoxylated flavonoids, sesquiterpene compounds such as tomentosin, and dicarboxylic acids, which may explain the observed bioactivity. Plant extracts obtained through sustainable methodology can be effective in biological agricultural applications.